1985
DOI: 10.1002/joc.3370050306
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale features of satellite‐derived outgoing long‐wave radiation in relation to monsoon circulation over the indian region

Abstract: The monthly mean outgoing long-wave radiation data from June 1974 to May 1981 were analysed for dominant eigenvector patterns. The first three eigenvector patterns explain nearly 93 per cent of the total variance. The first eigenvector pattern exhibits an annual cycle with a pronounced variation in the outgoing long-wave radiation over the tropical belt between lo" and 2WN. This is largely indicative of strong seasonal shift of the major area of cloudiness associated with the Intertropical Convergence Zone. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The outgoing longwave radiation (OLR) is considered as an indicator of convection (Krishnamurti et al, 1989;Murakami, 1980) and is essential for monsoon circulations (Chaudhari et al, 2010;Prasad & Verma, 1985). Clouds play a seminal role in regulating OLR through the warming (cooling) effect by high (low) level clouds (Chaudhari et al, 2018(Chaudhari et al, , 2019.…”
Section: Outgoing Longwave Radiation (Olr)mentioning
confidence: 99%
“…The outgoing longwave radiation (OLR) is considered as an indicator of convection (Krishnamurti et al, 1989;Murakami, 1980) and is essential for monsoon circulations (Chaudhari et al, 2010;Prasad & Verma, 1985). Clouds play a seminal role in regulating OLR through the warming (cooling) effect by high (low) level clouds (Chaudhari et al, 2018(Chaudhari et al, , 2019.…”
Section: Outgoing Longwave Radiation (Olr)mentioning
confidence: 99%
“…It has already been stated that low values of OLR corresponds to strong convective activities in the lower atmosphere and maybe the possibility of precipitation (Prasad and Verma 1985;Arkin et al 1989;Xie and Arkin 1998;Prasad et al2000;Kumar et al 2021). So, the inverse relation between OLR and precipitation could be a tool to understand the behaviour of CP and LSP.…”
Section: Outgoing Longwave Radiation (Olr)mentioning
confidence: 97%
“…Since both types of precipitation are associated with convective activity, the LSP and CP may relate with the Outgoing Longwave Radiation (OLR). Earlier researchers (Heddinghaus and Krueger, 1981;Prasad and Verma, 1985;Muthuvel and Arkin, 1992;Xie and Arkin 1998;Kumar et al, 2021) have shown that the low value of OLR corresponds to intense convection whereas a high value of OLR shows cloud-free regions and therefore used for the study of the variability of precipitations. Therefore there may be the possibility of a link between the OLR and the variability in CP and LSP.…”
Section: Introductionmentioning
confidence: 99%
“…The OLR data have been extensively used, apart from studying the earth radiation budget, in monitoring and understanding the tropical circulation changes and in modelling. Some examples are Murakami (1980), Prasad and Verma (1985), Horel et al (1989), Chelliah and Arkin (1992), Kousky and Kayano (1994) and Moron (1995).…”
Section: Introductionmentioning
confidence: 99%